Ontogenetic changes in skeletal muscle fiber type, fiber diameter and myoglobin concentration in the Northern elephant seal (Mirounga angustirostris) - Moore, Colby D.; Crocker, Daniel E.; Fahlman, Andreas; Moore, Michael J.; Willoughby, Darryn S.; Robbins, Kathleen A.; Kanatous, Shane B.; Trumble, Stephen J. (Frontiers in Physiology, 2014)
Northern elephant seals (Mirounga angustirostris) (NES) are known to be deep, long-duration divers and to sustain long-repeated patterns of breath-hold, or apnea. Some phocid dives remain within the bounds of aerobic metabolism, accompanied by physiological responses inducing lung compression, bradycardia and peripheral vasoconstriction. Current data suggest an absence of type IIb fibers in pinniped locomotory musculature. To date, no fiber type data exist for NES, a consummate deep diver. In this study, NES were biopsied in the wild. Ontogenetic changes in skeletal muscle were revealed through succinate dehydrogenase (SDH) based fiber typing. Results indicated a predominance of uniformly shaped, large type I fibers and elevated myoglobin (Mb) concentrations in the longissimus dorsi (LD) muscle of adults. No type II muscle fibers were detected in any adult sampled. This was in contrast to the juvenile animals that demonstrated type II myosin in Western Blot analysis, indicative of an ontogenetic change in skeletal muscle with maturation. These data support previous hypotheses that the absence of type II fibers indicates reliance on aerobic metabolism during dives, as well as a depressed metabolic rate and low energy locomotion. We also suggest that the lack of type IIb fibers (adults) may provide a protection against ischemia reperfusion (IR) injury in vasoconstricted peripheral skeletal muscle.